Predictors of mortality with multisystem inflammatory syndrome in children (MIS-C): A single centre prospective observational study from Eastern India - Bijay Kumar Meher; Isha Panda; Jyoti Prakash Sahoo; Geetachand Acharya; Martina Mohanty; Sarthak Naik; Pradeep Kumar Jena; Nirmal Kumar Mohakud (Wolters Kluwer Medknow Publications, 2023)
Background: Many cases of multisystem inflammatory syndrome in children (MIS-C) are reported in post-COVID-19 cases. It is a serious complication of COVID-19, with a high mortality rate in low-income countries compared to high-income countries. This study was conducted to find out predictors of mortality in MIS-C. Subjects and Methods: In this prospective observational study, 81 children with MIS-C were enrolled. Detailed clinical features, laboratory parameters, treatment, and outcome of cases were recorded. After the determination of individual factors associated with mortality by univariate analysis, a binary logistic regression model of significant factors associated with mortality was developed. Results: Fever, breathlessness, conjunctivitis, and pain abdomen were major presenting complaints at admission. Fifty-seven (70.3%) were presented with shock, of which 31 (54.4%) had normotensive shock and 26 (45.6%) had hypotensive shock. There were 8 (9.8%) deaths in the study group. Association of pneumonia, acute respiratory distress syndrome, and acute kidney injury were significantly high among nonsurvivors. Levels of lactate dehydrogenase (LDH), interleukin-6, and prothrombin time (international normalized ratio) were significantly higher in nonsurvivors than survivors. On binary logistic regression, raised LDH and the use of a mechanical ventilator were found to be independent predictors of death (P < 0.05). Conclusions: Shock was the predominant manifestation in children with MIS-C. Raised LDH and the use of mechanical ventilators were found to be independent predictors of death in cases of MIS-C.